Increasing Side-Style Style Side Shot Learning Outcomes using The Play Approach and Modification Media in High School Students - Ilham Widi Rahmansyah; Sabaruddin Yunis Bangun (Journal Physical Education, Health and Recreation, 2021)
This study aimed to determine the improvement of sideways style bullet repulsion learning outcomes using the play approach and modified media in class VII students of YPI Amir Hamzah Middle School Medan in the 2018/2019 academic year. The subjects in this study were students of class VII-I with a total of 24 students. The method used in this research is Classroom Action Research using a quantitative approach. The results of the study: (1) From the initial data, the sideways style shot put the overall attitude of 176 with an average of 7.33, obtained as many as seven students (29.17%) had reached the level of mastery learning while 17 students (70.83 %) did not meet the expected classical completeness criteria, namely 75% (2) From the first cycle learning outcomes test, the total number of attitude results assessed was 204 with an average score of 8.5 as many as 17 students (70.83%) have reached the level of mastery learning while seven students (20.17%) have not reached the level of completeness of learning. However, it has not met the expected classical completeness criteria of 75% (3). From the second cycle of learning outcomes tests, the total number of attitude results assessed is 224, with an average of 9.33. As many as 21 students (87.5%) have completed the learning, and three students (12.5%) are still not complete. Based on the results of these tests, there was an increase in the number of students who had achieved mastery of learning and met the criteria for classical completeness, namely 85%. In this case, it can be seen that there was an increase in the value from cycle I to cycle II. The conclusion of the study is that the application of the play approach and modified media can have an influence in an effort to improve the learning outcomes of sideways style shots put in class VII-I SMP Amir Hamzah Medan in the 2018/2019 academic year.